Biological facilitation of the giant tree fern Angiopteris evecta in the germination of the invasive velvet tree Miconia calvescens - Lee,Jaemin (PeerJ Preprints, 2017)
Background. Biological facilitation is a type of relationship between two taxa that benefits at least one of the participants and harms neither. Although invasive species are widely known to compete with native taxa, recent studies suggest that invasive and native species can have positive relationships. This study aims to examine the biological facilitation of the germination of invasive Miconia calvescens by giant tree fern Angiopteris evecta, native to French Polynesia. Methods. Field surveys were conducted to measure A. evecta and M. calvescens by applying the 10×10 m2 quadrat survey method. The density of seedlings, saplings, and matures of M. calvescens growing on the rhizomes of A. evecta and on bare soil was compared, and the correlation between the size of the rhizomes and the number of M. calvescens growing on them was verified. Two separate sets of nutrient measurements of substrates were performed to compare the nutrient of A. evecta rhizome and other environments (abiotic and potential biotic environments). Leaf decomposition rate of five dominant tree species was compared to verify whether A. evecta has quickly decomposing leaves, and therefore induce the germination of M. calvescens indirectly. Results. Field surveys show that there is a greater number of seedlings and saplings of M. calvescens growing on the rhizomes of A. evecta as compared to bare soil. Furthermore, there is a positive correlation between the size of rhizomes and the number of M. calvescens growing on them. Substrates of A. evecta had higher phosphorus and potassium contents compared to other soils and substrates, but did not differ from bark of other tree species that could potentially offer favorable microenvironments. A. evecta has quickly decomposing leaves. Discussion. A. evecta facilitates the germination of M. calvescens, supported by the much higher number of seedlings and saplings growing on the rhizomes and the positive correlation between the size of the rhizome and the number of M. calvescens growing on it. Microslopes on the rhizomes of A. evecta prevent leaf litter from accumulating on the rhizomes, and enable more sunlight to reach and facilitate the germination of M. calvescens seeds. Also, quickly decomposing leaves of A. evecta prevent the accumulation of leaf litter on the ground and enable more light to reach seed bank. Although the chemical components is not different from other tree species, physical structure of the rhizome and consequent higher light availability, and higher amount of potassium than bare soil would be the possible reason for the facilitation. Biological facilitation of the germination of invasive M. calvescens by native A. evecta can give better understanding on the invasion success and the relationship between the native and invasive species. Invasion of A. evecta can induce and promote further invasion of M. calvescens. Therefore, thorough management of ongoing invasion of A. evecta is particularly required.
Keywords: Biological facilitation; Nurse plants; Biological invasions; Miconia calvescens; Angiopteris evecta; Velvet Tree; invasive species